HUBUNGAN PENGETAHUAN AKSEPTOR DENGAN KEIKUTSERTAAN MENGGUNAKAN METODE KONTRASEPSI JANGKA PANJANG - Reka Shafna Wahyuningtyas; Shinta Kristianti; Lumastari Ajeng Wijayanti (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Long-term contraception is a method of contraception that can be used for a relatively long time. The use of long-term contraceptive methods as an important role in reducing fertility rates. One of the factors that influence the use of long-term contraceptive methods is knowledge. Knowledge is very important to change the behavior of acceptors to use long-term contraceptives. This study is to analyze and review journals related to the relationship between acceptor knowledge and participation in using long-term contraceptive methods. This literature study used a comparison system, namely a review system by looking for a similarity in the journal's literature, the researcher will draw a conclusion according to the specific purpose. Keywords (“Knowledge” OR “Acceptor” OR “Participation” OR “MKJP). Using google scholar, pubmed, and proquest databases. The result of identifying the knowledge of the acceptor, found 11 journals that discussed the level of knowledge of the acceptor,8 of 11 journals in addition to discussing the level of knowledge also discuss husband support, education, and family support. Analyzing the knowledge of acceptors with participation in using long-term contraceptive methods in terms of quantity, it was found that 10 journals stated p value < 0.05 which indicated that there was a relationship between knowledge of acceptors and participation in using long-term contraceptive methods. 1 journal states p value > 0.05 which indicates that there is no relationship between knowledge and participation in the long-term contraceptive method. The results of the study of acceptor’s knowledge can affect participation in using long-term contraceptive methods.